Genetic variability in the regulation of gene expression in ten regions of the human brain - Ramasamy, Adaikalavan; Trabzuni, Daniah; Guelfi, Sebastian; Varghese, Vibin; Smith, Colin; Walker, Robert; De, Tisham; Coin, Lachlan; de Silva, Rohan; Cookson, Mark R; Singleton, Andrew B; Hardy, John; et al. (Nature neuroscience, 2014)
Expression quantitative trait loci (eQTLs) are genomic regions that regulate gene expression. Here the authors provide a publicly available data set of exon-level eQTLs across the human brain. This includes many genome-wide association study (GWAS) hits for neurological and psychiatric disorders. Germ-line genetic control of gene expression occurs via expression quantitative trait loci (eQTLs). We present a large, exon-specific eQTL data set covering ten human brain regions. We found that cis -eQTL signals (within 1 Mb of their target gene) were numerous, and many acted heterogeneously among regions and exons. Co-regulation analysis of shared eQTL signals produced well-defined modules of region-specific co-regulated genes, in contrast to standard coexpression analysis of the same samples. We report cis -eQTL signals for 23.1% of catalogued genome-wide association study hits for adult-onset neurological disorders. The data set is publicly available via public data repositories and via http://www.braineac.org/ . Our study increases our understanding of the regulation of gene expression in the human brain and will be of value to others pursuing functional follow-up of disease-associated variants.